The Analysis of Covid-19 Impact on Catfish Hatchery Businnes (Clarias sp.) in Baros District, Serang Regency, Banten Province - Wulandari, Cynthia Kusuma; Mustahal, Mustahal (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The pandemic conditions caused by the Corona virus in 2020 had a global impact, including the catfish hatchery business sector in the community. Based on this, a study was conducted that aims to analyze the impact of Covid-19 on the income, expenditure, and marketing of catfish hatchery business, especially in Baros District, Serang Regency, Banten. This study used the direct data collection techniques, field observations and interviews with 12 (twelve) catfish hatcheries in December 2021. Secondary data came from the Central Statistics Agency (BPS) for Baros District in 2019-2020. The results showed that 50% of respondents experienced a decrease in income during the Covid-19 pandemic. The decrease in revenue from the catfish hatchery during Covid-19 ranged from 12.50 - 66.67% compared to the income before the Covid-19 pandemic. In addition, farmers' expenditures have increased due to rising feed prices. Expenditure on feed prices by the highest cultivators is IDR 8,060,000 and the lowest is IDR 880,000 per cycle. The costs incurred are based on the type of feed in hatchery activities, namely Tubifex sp. by 33%, fengli by 12%, pf 500 by 19%, pf 800 by 17%, pf 1000 by 19% during one cycle. The size of catfish seeds sold is 2-7 cm with a price range of IDR 100 - 200 per head. Catfish farmers are experiencing difficulties in marketing their seeds due to restrictions on mobility during the pandemic. Changes in consumer behavior have resulted in a decrease in direct buying interest.